Hak Asuh Anak (Hadhanah) bagi Ibu yang Menikah lagi Prespektif Maqashid Syari’ah - Faizzati, Savvy Dian (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
Child custody (Hadhanah) is a crucial issue in Islamic law, particularly when a mother with custody remarries. Differences in scholars' opinions and the varying decisions of religious courts in Indonesia highlight the need for an in-depth analysis through the perspective of maqashid syariah. This study aims to examine child custody for remarried mothers by emphasizing the protection of life (hifz an-nafs), lineage (hifz an-nasl), and child welfare. The research employs a qualitative approach using library research and comparative analysis of scholars' views and court rulings. The findings indicate that custody decisions should not solely rely on classical legal texts but must also consider the child's well-being. This study contributes by providing a more comprehensive understanding of child custody in Islam and offering recommendations for policymakers and legal practitioners to apply maqashid syariah principles in custody cases, ensuring decisions prioritize the best interests of the child.